Pengaruh Customer Online Review Dan Kepercayaan Terhadap Keputusan Pembelian Furniture Kudu Kayu Di Instagram Pada Workshop Parung Panjang - Bogor - Della Amalia Putri; Ali Mubarok (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of customer online reviews and trust on purchasing decisions of Kudu Kayu Furniture on Instagram at the Parung Panjang Workshop, Bogor. This research uses a quantitative method with a saturated sampling technique, resulting in a sample of 75 respondents who have purchased Kudu Kayu Furniture through Instagram. Data were collected using questionnaires, while data analysis techniques included validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing using SPSS software. The results indicate that partially customer online reviews have a positive and significant effect on purchasing decisions, with a t value of 5.260 greater than the t table value of 1.933 and a significance value of 0.000 < 0.05, with a coefficient of determination of 27.5%. Trust also has a positive and significant effect on purchasing decisions, with a t value of 4.832 greater than the t table value of 1.993 and a significance value of 0.000 < 0.05, and a coefficient of determination of 24.2%. Simultaneously, customer online reviews and trust have a positive and significant effect on purchasing decisions, as indicated by an F value of 21.682 greater than the F table value of 3.12 and a significance value of 0.000 < 0.05. The simultaneous coefficient of determination of 37.6% indicates that customer online reviews and trust jointly influence purchasing decisions, while the remaining percentage is influenced by other factors outside this study. Therefore, customer online reviews and trust are important factors in influencing purchasing decisions for Kudu Kayu Furniture through Instagram